Study on the Formation of Cs-U-O from the Reaction between Cs2O and UO2 - Kim, Jong-Goo; Jang, Eunsil; Park, Yang-Soon; Ha, Yeong-Keong; Song, Kyuseok (Asian Journal of Chemistry, 2013)
Reactions between UO2 and Cs2O in various Cs/U compounds (atom ratios: 0.5 3.0) were investigated in a temperature range of 30 to 1100 ºC using a thermogravimetric analyzer and differential scanning calorimeter. The formation of Cs-U-O was determined by the appearance of exothermic peaks at 186 ºC and 240 ºC in differential scanning calorimeter and weight loss depending on the Cs/U ratio from 200 ºC to 250 ºC and from 610 ºC to 710 ºC when using a TGA. By chemical analysis, it was determined that the formation of Cs-U-O increased linearly with the Cs/U ratio. From X-ray diffractometer measurements, diffraction patterns of Cs2UO4 and Cs2U2O7 were observed when heated to 500 ºC and 1100 ºC, respectively.